Treatment Outcome of Diabetic Foot Based on the Control of Random Blood Glucose and HbA1c in BIRDEM General Hospital, Dhaka, Bangladesh (Delta Medical College Journal, 2020)
Background: Diabetic foot is a common and potentially disastrous complication that can rapidly progress to irreversible septic gangrene, necessitating foot amputation.Objectives: To assess the clinical outcome of treatment of diabetic foot in diabetic patients based on random blood glucose (RBG) and HbA1c level.Materials and method: This prospective observational study was conducted in the Department of Surgery, BIRDEM General Hospital, Shahbag, Dhaka, Bangladesh, from July 2018 to December 2018. A total of 350 patients with diabetic foot were enrolled in the study based on inclusion and exclusion criteria. The patients were divided into four groups based on RBS and HbA1c level. A complete history was taken, thorough clinical examination was done and relevant investigation reports were collected. Collected data were classified, edited, coded, and entered into the computer for statistical analysis using SPSS version 23.Results: Mean age was 47.6±13.3 years in group A, 48.2±12.7 years in group B, 46.7±13.1 years in group C, and 49.9±12.5 years in group D. Male to female ratio was 2.3:1 in group A, 3.5:1 in group B, 1.5:1 in group C and 2.9:1 in group D. One hundred eight patients were found to have Wagner ulcer grading I. Among them, 2(20.0%) were in group A, 9(33.3%) were in group B, 12(36.4%) were in group C, and 85(30.4%) were in group D. Twenty-two patients were found to have Wagner ulcer grading IV. Among them, 1(3.0%) of group C and 21(7.5%) of group D. The difference was statistically significant (p